Richard III palimpseste. Richard III de Verhelst mis en scène par Lagarde : l'ellipse du champ de bataille - Florence March (Sillages Critiques)
Flemish playwright Peter Verhelst's adaptation of Richard III - as staged by French director Ludovic Lagarde at the Avignon Festival in 2007 - deletes the entire last act of the play, the act that, in the Shakespearean original, dramatises the battle of Bosworth. This omission, I wish to argue, crystallises - in the space between page and stage - the choice of what I call an "aesthetic of the suture", or rather of the impossibility of the suture, which I offer as a dialectical metaphor for the relationship between hypo- and hyper-texts. Since, in Shakespeare's history plays, the representation of war offers a systematic source of metatheatre, I will focus for my analysis of this production on Verhelst's and Lagarde's alternative metatheatrical strategies, in the absence of an actual battlefield, for presenting the text's "blood narrative".